Growth Response and Results of White Oyster Mushroom (Pleurotus ostreatus) due to Additional Concentration Molasse and Rice Flour in Media Baglog - Nasution, Khairi Amri; Warsito, Kabul; Hafiz, Muhammad (Universitas Labuhanbatu, 2022)
White oyster mushroom (Pleurotus Ostreatus) is a type of wood fungus. The purpose of this study was to determine the growth response of white oyster mushroom (Pleurotus ostreatus) due to the addition of molasses and rice flour. This research was conducted at the Center for Breeding and Development of Oyster Mushroom and Ear Mushroom Cultivation Sunggal District, Deli Serdang Regency. This study used a factorial completely randomized design (RAL) consisting of 2 treatment factors, 16 treatments, 2 replications and 32 baglogs. The first factor is the concentration of molasses with M0: (control), M1: 7.5 ml/20 ml, M2: 15.0 ml/20 ml, M3: 22.5 ml/20 ml and the second factor is the administration of Rice Flour with a concentration of T0: (control), T1: 20 gr/20 ml, T2: 40 gr/20 ml, T3: 60 gr/20ml. Parameters observed were mycelium growth rate (cm), stalk height (cm), hood diameter (cm), hood thickness (mm), number of branches/clumps, and wet weight (g). The rice flour treatment 12 days after inoculation showed significantly different results with the highest data T0: 10.13cm and the lowest data T3: 8.00cm. The highest data was T0:14.85cm and the lowest data was T3: 12.36cm after 18 days after inoculation. The highest parameter of plant height was M0: 20.13cm and the highest data of rice flour treatment was T2: 19.13 cm. The hood diameter parameter showed the highest data was M2: 43.90cm and the highest rice flour treatment data was T2: 2.64cm. The highest data hood thickness parameters are M2: 29.09mm and T2: 29.98 mm. parameters of the highest number of data branches M0: 88.75 branches and T1: 86.25 branches. The highest data wet weight parameter was M0: 88.75 grams and the highest data was given to rice flour at T1: 86.25 grams